Communicative Behavior Retrospective Patterns Among Students During Lab Practice - Carrillo, Edgardo Ruiz; Meraz, Samuel (Advances in Social Sciences Research Journal, 2014)
The aim of this work is to detect the existence of communicative interaction patterns among Biology students during lab practice. This, based on the analysis of the conversations held among them. Observational methodology was used. An iterative and detailed category system thoroughly was developed as an observation tool, and was later put through a process of re-categorization. A total of six sessions were observed; each one lasting one hour. The intercessional sequential analysis was used with the aid of the program SDIS-GSEQ. The results show that it is highly important for the students the use of question-answer (IAE) in its different modalities: first, in probability of occurrence, are the categories of Persuading and Proposing, the next significant sequential probabilities are: Evaluating, Confirming, and Confusing; followed in sequential occurrence order by: Arguing, Classifying, Correcting, Clarifying, and Suggesting. Last in sequential inhibitory occurrence are: Creating an Opinion, Directing, and Evaluating. These are the particular ways in which students encourage participation during lab practice, opening their minds to their classmates’ feedback, leading to questions and answers that create new discussion topics and increase learning opportunities.